Associação de anticorpos leucocitários em indivíduos com aloimunização eritrocitária - Martins, Juliana Oliveira [UNIFESP] (2017)
Background: Leukocyte antibodies against HLA class I, class II and human neutrophil antigens (HNA) are formed from exposure to these antigens by transfusion, pregnancy or transplant, and may be associated with transfusion-related acute lung injury (TRALI) and immune neutropenias. Risk factors for acquisition of leukocyte antibodies are yet to be determined and present great importance for the prevention of severe and fatal transfusion reactions. Aims: To compare the prevalence of leukocyte antibodies in women with or without red blood cell (RBC) alloimmunization. Methods: This transversal study included women whose only stimulus to alloimmunization was pregnancy, with no transfusion history. We analyzed 147 blood samples from women with RBC alloimmunization, confirmed by the investigation and identification of RBC antibodies by the DG Gel-Card technique (Grifols-Spain). The control group consisted of 563 blood donors women with pregnancy history but without RBC alloimmunization. The identification of leukocyte antibodies was performed by: 1) granulocyte agglutination test (GAT), 2) white cell immunofluorescence test (Flow-WIFT), both tests using a panel of neutrophils obtained from three donors with previous HNA genotyping, and 3) bead-based assay - LABScreen Multi (LSM) (One Lambda), capable of detecting antibodies against HNA-1a, -1b, -1c, -2, -3a, -3b, -4a, -5a, -5b and HLA class I and II antigens. The identified HNA antibodies were confirmed by genotyping the corresponding antigen. Results: In the cohort of women with RBC alloimmunization we found 178 RBC antibodies: anti-D (anti-Lea (25.3%), anti-D (24.7%), anti-C (9.0%), anti-E (9.0%), anti-K (5.6%) and other antibodies (26.4%). We identified 74/147 (50.3%) samples with anti-HLA antibodies and 11/147 (7.5%) samples with anti-HNA antibodies with the following specificities: 5/11 anti-HNA-1a, 2/11 anti-FCRɣIIIb and 4/11 anti-HNA-3b. In the control group, we found 238/563 (42.3%) samples with anti-HLA and 24/563 (4.3%) samples with anti-HNA: 8/24 anti-HNA-1a, 1/24 anti-HNA-1c, 3/24 anti-HNA-2, 2/24 anti-HNA-3a, 5/24 anti-HNA-3b, 3/24 anti-HNA-5a and 2/24 anti-HNA-5b. Regarding the gestational history, 82/147 (55.8%) women in the group with RBC alloimmunization and 493/563 (87.6%) in control group had two or more pregnancies. The statistical analysis was performed in total samples, regardless the number of pregnancies, however no significant difference was observed in the prevalence rate of anti-HNA and anti-HLA between the two groups (p=0.10 and p=0.07, respectively). When the analysis was stratified including only multiparous women (two or more pregnancies) the prevalence of HNA alloimmunization was statistically significant in the group of women with RBC alloimmunization: 9/82 (11%) versus 23/493 (4.7%) blood donors, p=0.02, OR=2.52 (95% CI=1.15-3.79). Similarly a higher prevalence of HLA antibodies in the group of multiparous women with RBC alloimmunization was also observed: 51/82 (62.2%) versus 224/493 (45.4%), p=0.004, OR=1.97 (95% CI=1.18-2.71). Conclusions: The data show that RBC alloimmunization was significantly associated with the development of antibodies against leukocytes (anti-HNA and anti-HLA). A higher frequency of HNA alloimmunization (11%) observed in the group of multiparous women with RBC alloimmunization compared to the control group (4.7%), suggest that they are better immune responders and that they react strongly to allogeneic exposure. Anti-HLA antibodies have often been found in plasma in southeastern Brazil female blood donors (42.3%), and are statistically associated with the number of pregnancy (p<0.001).